Opportunities and challenges in agriculture and garments: a general equilibrium analysis of the Bangladesh economy - Arndt, Channing; Dorosh, Paul A.; Fontana, Marzia; Zohir, Sajjad; El-Said, Moataz; Lungren, Christen (International Food Policy Research Institute, 2002)
For the past two decades, Bangladesh has enjoyed steady growth in per capita incomes enabling a significant reduction in poverty. An increase in rice productivity, achieved through a combination of improved seeds, increased fertilizer use, and public and private investments in irrigation, played a major role in the increase in incomes. Among the other major factors were a large expansion in textile exports, made possible by changes in world demand, Bangladesh trade liberalization, and macro-economic stability; and increases in workers remittances. In order to accelerate or even maintain income growth rates and poverty reduction, future policies must be carefully designed to capture the benefits and minimize the risks of international trade and a constantly changing international environment. A proper assessment of the impact of such policies and economic developments on the poor requires a comprehensive framework to analyze interactions between different sectors as well as linkages between macro and micro levels. In this paper we construct a social accounting matrix for 1999/2000 and develop a computable general equilibrium model (CGE) with special treatment of the rice and wheat sectors. We then present simulations of the effects of (i) rice productivity shocks, (ii) a decline in the world rice price, and (iii) a reduction in RMG exports, reflecting an end to preferential access to RMG markets for Bangladesh goods.... Overall, these simulations illustrate the importance of trade policy and links between Bangladesh and the world economy. International trade offers the potential to prevent a decline in real prices of rice if productivity of paddy production increases and to benefit from increased export earnings. It has also permitted a large increase in RMG export earnings. However, changes in international markets could threaten welfare of some Bangladesh households, as well, as illustrated by the simulations of lower import prices of rice that could sharply reduce farmer incomes, and of a decline in textile export earnings that could sharply reduce female urban employment and urban household incomes....[T]hese simulations show that the Bangladesh economy and household incomes are clearly linked with the global economy, particularly through foodgrain trade and the RMG sector. Efforts to alleviate poverty and raise the incomes of the poor should not neglect these linkages, particularly in cases where these poverty alleviation interventions are large enough to have major effects on the real exchange rate and female labor earnings." -- Author's Abstract.